2001
DOI: 10.1590/s1516-31802001000500007
|View full text |Cite
|
Sign up to set email alerts
|

Complete atrioventricular block during renal transplantation in a patient with Alport's syndrome: case report

Abstract: system disturbances, some degree of atrioventricular block, including complete atrioventricular block, can occur. In this situation, a transcutaneous pacemaker provides rapid and effective treatment in the operating room, thereby permitting the planning of a definitive treatment. KEY WORDS: KEY WORDS: KEY WORDS: KEY WORDS:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Similarly, transient complete AV block during renal transplantation was reported by Ferrari et al. (7). They concluded that transient complete AV block may occur because of abnormalities in calcium metabolism leading to fibrosis in the conduction system or myocardial calcification.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, transient complete AV block during renal transplantation was reported by Ferrari et al. (7). They concluded that transient complete AV block may occur because of abnormalities in calcium metabolism leading to fibrosis in the conduction system or myocardial calcification.…”
Section: Discussionsupporting
confidence: 68%
“…71 Hyperkalaemia and calcium channel blockers may contribute to the development of complete AV block, as may epidural anaesthesia, with its attendant reduction in sympathetic activity. 41 Hypertension may be the primary cause of kidney disease or the result of renal parenchymal or renovascular disease. Arterial pressure control and block of the RAS are important in preserving residual function in patients with both diabetic and non-diabetic renal disease.…”
Section: Filler Equationmentioning
confidence: 99%
“…CKD can lead to fibrosis and calcification of the cardiac conduction system by disrupting calcium metabolism and cause degenerative CSD. [ 19 ] Therefore, bradyarrhythmia can persist, although hyperkalemia was corrected. In addition, in about a fifth of patients with extrinsic etiology, hyperkalemia was accompanied by drug therapy.…”
Section: Discussionmentioning
confidence: 99%